PENGARUH KELEMBABAN DAN ALKALISASI SERAT TERHADAP KEKUATAN GESER KOMPOSIT RAMI-POLIESTER - SARJANADI DAMANIK , FERDINANDUS
The use of natural fiber reinforcement in polymeric composites is potential as an alternative to replace the synthetic glass fiber. However, the interface property of the natural fiber and the matrices is an important point that must be considered. The fiber-matrix interface plays an important role in determining the mechanical properties of the composites. The interface is normally affected by the environment, particularly due to the hydrophobic nature of the natural fibers. This research observes the influence of humidity and fiber alkalization to the interface properties of ramie fiber composite-polyester. The alkalization is used to increase the mechanical interlocking properties between fiber and matrix. The interlaminar shear strength resulting from short beam test is used to examine the interfacial property. SEM (scanning electron microscope), image analysis and water absorption analysis are carried out to observed the composite's microstructure in relation with the physical property of the interface. The effect of humidity is conditioned at RH 60 and RH 95. The humidity will effect to the shear strength of the ramie-polyester composite. A higher humidity decreases the composites shear strength (37-48%) due to swelling and interfacial degradation. The fiber alkalization and the increase of NaOH concentration during alkalization will increase interface strength on Rh 60 (0.5-40.4%) and Rh 95 (25.1-39%). Environmental resistance of the ramiepolyester composites increase 10.3%. Amount of matriks on fiber, when composite shear test applied, shows the effect of alkalization. It will appear on SEM results. This phenomena shows that increasing at mechanical interlocking will cause increasing at interface strengthening. In this research, void ini composit still influence composite shear strength (7.5-20.3%). Composite shear strength will decrease when void volume increase.